Quality of life considerations in head and neck cancer: United Kingdom National Multidisciplinary Guidelines. (May 2016) - Rogers, S N; Semple, C; Babb, M; Humphris, G
Abstract: This is the official guideline endorsed by the specialty associations involved in the care of head and neck cancer patients in the UK. It identifies the current evidence base and role of health-related quality of life assessment for this group of patients. Recommendations: Health-related quality of life is integral to treatment planning, refining treatment protocols, and more personalised follow-up support. (G) Health-related quality of life and patient concerns should be regularly assessed during patient care. (G) Health-related quality of life assessment and patient concerns on an individual patient basis can be helpful to trigger multi-professional support and interventions. (G)